The STEAM Approach: Implementation and its Effect on Students’ Motivation and Learning Outcomes - Khusnaini, Natasya Lailatul; Wulandari, Fitria (Papanda Publisher, 2025)
The rapid development of technology in the era of the industrial revolution 4.0 has brought significant changes to the world of education. One of the main challenges faced is how to improve learning motivation and learning outcomes of students through an innovative approach that is relevant to the times. In the context of science learning, particularly on the topic of energy transformation, an appropriate instructional approach has a significant impact on students’ motivation an learning outcomes. One effort that can be made is through learning with the STEAM approach (Science, Technology, Engineering, Art, and Mathematics). The purpose of this study was to determine the implementation and test the effect of the STEAM approach in science subjects on energy changes on student motivation and learning outcomes. This study used a quantitative quasi-experimental design with a one group pretest-posttest design. The population in this study were grade IV students of SDN Kemangsen 1 Krian, the sample used was 30 grade IV students. The data analysis technique used the paired sample t-test. The results of the pretest and posttest hypothesis tests showed a sig. (2-tailed) value of 0.00 which is less than 0.05 so that there is a significant effect of the STEAM approach on student motivation and learning outcomes. Thus, it can be concluded that the STEAM approach can be used as an alternative learning, especially in science subjects on energy changes in relation to student motivation and learning outcomes.